De la Nouvelle-Angleterre à la Nouvelle-France: l'histoire des captifs anglo-américains au Canada entre 1675 et 1760 - Fournier, Marcel (Société généalogique canadienne-française, 1992)
Keywords: Américains; Captifs

The Montreal Militia as a Social Institution before World War I - Miller, Carman (Urban History Review / Revue d'histoire urbaine, 1990)
Keywords: Milice

The Fortifications of Montreal 1717-1744: the Development and Implementation of the Plan - Poirier, Monique (Université Concordia, 1991)
Keywords: Fortifications

Entente cordiale? La section montréalaise du Fonds patriotique canadien, 1914-1923: le bénévolat de guerre à Montréal - Morton, Desmond (Revue d'histoire de l'Amérique française, 1999)
Keywords: Bénévolat; Guerre

De Jeanne D'Arc à Madeleine de Verchères: la femme guerrière dans la société d'Ancien Régime - Gervais, Diane; Lusignan, Serge (Revue d'histoire de l'Amérique française, 1999)
Keywords: Combat; Femmes; Forts

Les drapeaux militaires en Nouvelle-France - Chartrand, René (Material History Review / Revue d’histoire de la culture matérielle, 1995)
Keywords: Armée

Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

Les milieux d'affaires francophones de Montréal face à la Première Guerre mondiale - Villerbu, Tangi (Université de Rennes 2, 1996)
Keywords: Francophones; Guerre; Hommes d'affaires

City at War: The Effects of the Second World War on Verdun, Québec - Durflinger, Serge Marc (Université McGill, 1997)
Keywords: Guerre; Quartiers; Verdun

Le mouvement ouvrier montréalais et la crise de la conscription 1916-1918 - Dansereau, Bernard (Université du Québec à Montréal, 1994)
Keywords: Conscription; Guerre

Les quatre couleurs de Radisson: explorer aujourd'hui le XVIIe siècle - Fournier, Martin (Université Laval, 1998)

Guerre et censure: l'expérience des journaux, des militaires et de la population pendant la Deuxième Guerre mondiale - Beauregard, Claude (Université Laval, 1995)
Keywords: Guerre; Journalistes

Ne faire qu'un seul peuple? Iroquois et Français à l'"âge héroïque" de la Nouvelle-France (1600-1660) - Beaulieu, Alain (Université Laval, 1992)
Keywords: Autochtones; Français; Iroquois

Captives in Canada, 1744-1763 - Gray, Colleen (Université McGill, 1993)
Keywords: Autochtones; Britanniques; Captifs